Lean Management Implementation Training at The Pharmaceutical Unit of Islamic Hospital in Surabaya - Agus Aan Adriansyah; Budhi Setianto; Akas Yekti Pulih Asih; Iqbal Firdaus; Nikmatus Sa'adah; Muhammad Zahid Abdillah (To Maega : Jurnal Pengabdian Masyarakat, 2022)
Lean management is one of the sufficient methods often used by an organization, company or agency certain. this method is claimed capable to make a company capable increase the quality of the product more efficient. The problems faced by the Surabaya Islamic Hospital are: Currently, the difference cost operational with income at RSI Surabaya A. Yani is only 15%-17%, while policy directors want a difference the can to 30%, The goal of devotion Public this give Lean management training at the Pharmacy Unit of the Surabaya Islamic Hospital expected training this could give benefit related to governance effective and efficient pharmacy so that could increase quality service and profitability. Training this use method lecture, discussion as well as simulation involving 18 workers from the pharmacy unit consisting of 5 Pharmacists and 13 pharmacists. From devotion Public this There are much Lean Management Training at the Pharmacy Unit of the Surabaya Islamic Hospital give benefit to participants, increase knowledge increasing participants by 18% expected could make more service effective and efficient that could increase quality service and profitability.